Vocational education and training program design and employability outcomes: A systematic review and bibliometric analysis of school-to-work outcomes - Kharel, Suman; Dahal, Rewan Kumar; Joshi, Surendra Prasad (Journal of International Students, 2026)
This study synthesizes international research from 2015 to 2025 to evaluate how effective vocational education and training (VET) programs help students achieve sustainable employment. It combines a systematic review of 55 sources with a bibliometric analysis of 7,469 publications using VOSviewer and Dimensions.ai. Employment outcomes ranged widely, from 93% placement rates in Saudi Arabian healthcare VET to 43% competency-matched employment in Indonesia. No pooled effect size was estimable due to heterogeneity in outcome measurement; however, six randomized controlled trials from Sub-Saharan Africa reported positive employment odds among youth, with effects strongest within 12 months of program completion. Fundamental employability skills, including creativity, adaptability, and problem-solving, consistently emerge as key drivers of successful school-to-work transitions. However, post-program support and the alignment between the curriculum and the industry remain major obstacles that need to be addressed. VET programs succeed when they collaborate with local industries.